Patterns of conflict-related trauma exposure and their relation to psychopathology: A person-centered analysis in a population-based sample from eastern DRC - Lars Dumke; Roos van der Haer; Carlo Koos; Tobias Hecker (Elsevier, 2021)
Populations in war-torn regions are exposed to a wide array of traumatic events that can cause an enormous psychological burden. Individual characteristics influence the likelihood of being exposed to certain events, pointing to systematic interindividual differences in trauma exposure. However, there is a dearth of studies examining potential patterns of trauma exposure in war regions. In this cross-sectional epidemiological study, we applied a person-centered approach to identify patterns in the exposure to conflict-related traumatic events and determine their impact on commonly reported mental health problems in a population-based sample (N ​= ​1000) from the eastern Democratic Republic of Congo. We implemented multi-stage random cluster sampling to randomly select adults from 100 villages. Of 1000 adults (Mage ​= ​43.19 years) included in the study, 50% were female. Results showed high prevalence of PTSD (17.0%), depression (27.8%), anxiety (25.4%) and suicidality (15.1%) following exposure to conflict-related traumatic events since 2002. Latent Class Analysis identified three distinct classes of trauma exposure: Class 1 "low-trauma-exposure" (51.4%, n ​= ​514) was characterized by the lowest probabilities of trauma exposure. Class 2 "non-physical-trauma" (39.1%, n ​= ​391) consisted of individuals with a high probability for exposure to non-physical trauma types only. Class 3 "interpersonal-trauma" (9.5%, n ​= ​95) had the overall highest probability of exposure to traumatic events and was the only class affected by interpersonal-trauma types. Class membership was related to gender, age and place of living. Vulnerability to mental health problems increased from low-trauma-exposure to non-physical-trauma to interpersonal-trauma class. Our findings indicate that the exposure to traumatic events in conflict-affected populations underlies distinct patterns, with interpersonal trauma as a distinguishing marker. Vulnerability to psychopathology varies with trauma patterns, revealing patterns that include both non-physical and interpersonal traumata as most detrimental for mental health. Identification of underlying trauma patterns and their effects may improve mental health care in war-affected populations.